Production of glycerol carbonate from industrial grade crude glycerol via microwave-assisted transesterification / Teng Wai Keng - Teng , Wai Keng (2022)
This research aims to produce glycerol carbonate (GC) from industrial-grade crude glycerol originating from a biodiesel plant via microwave-assisted transesterification (MAT). Aspects including a feasibility study of transforming industrial-grade crude glycerol into GC via MAT, the study of the effect of impurities in the crude glycerol, process optimization, and kinetic study were investigated. Three types of glycerol, the pure form, crude glycerol at 70% and 86%, were transesterified with dimethyl carbonate (DMC) using CaO as a catalyst. A comparison study was made between conventional transesterification and MAT. The research found that crude glycerol of 70% purity produced higher GC yield in both conventional and MAT processes with the latter showing better energy efficiency. The highest GC yield of 93.4% was obtained from glycerol with a purity of 70% under MAT with 1 wt.% of CaO, 2:1 molar ratio of DMC/glycerol at 65 °C and 5 min reaction time. The yield of GC was observed to increase with temperature, time, and molar ratio but independent from the catalyst loading. The impact of single and multiple impurities in crude glycerol was investigated by adding impurities to pure glycerol. Methanol, sodium methylate, and soap were found to give a positive effect whereas water and fatty acid inhibited GC synthesis. The addition of impurities of 20 wt.% methanol and 1 wt.% sodium methylate increased GC yield by four times, from 7.62% to 30.56%. At its optimized reaction conditions, the GC yield can be further increased to 80.43% through the addition of 5 wt.% sodium methylate and 0.01 wt.% of soap. This shows the impurities which might otherwise be undesirable for the transesterification process under normal circumstances have unusually demonstrated positive effects on the performance of The MAT process was optimized to yield 99.5% GC from 70% purity crude glycerol at 65 °C with 1 wt.% catalyst loading in 5 min at a DMC/glycerol molar ratio of 2.5. As a comparison, MAT of pure glycerol was also carried out and the findings showed that merely 66.6% GC yield can be achieved at its longer reaction time of 60 min and higher catalyst loading of 6 wt.%. The reaction time is the most significant factor for MAT of both types of glycerol. MAT reaction fitted well to an irreversible second-order kinetic model. The values of rate constants between 45 °C to 65 °C were in the range of 2.34 - 2.59 x 10-2 L/mol.min, which is one order of magnitude higher than that of conventional heating. Furthermore, a relatively lower activation energy of 4.53 kJ/mol is needed for GC production via MAT of crude glycerol in comparison to the conventional transesterification process. The research demonstrated the feasibility of direct utilization of industrial-grade crude glycerol from biodiesel plants to produce GC. The microwaveassisted process effectively transformed crude glycerol into value-added GC, in addition to its cost-effectiveness in using biodiesel waste as raw material. Hence, compared to other reported transformation techniques, MAT of crude glycerol was shown to be an economically viable, sustainable, robust, and energy-efficient synthesis process of GC.